Extraction of Essential Oil from Moringa Oleifera Leaves Using Steam Distillation and Soxhlet Extraction Method - Haykal, Muhammad Husin; Trisnawan, Naufal Nafis; Wiguno, Annas; Kuswandi, Kuswandi (Jurnal Teknik Kimia dan Lingkungan, 2024)
Essential oil is one of Indonesia's agro-industrial export commodities, one of which is essential oil from Moringa oleifera leaves. This study aims to study the results of the yield and analyze the essential oil content of Moringa oleifera leaves using the steam distillation method and Soxhlet extraction using ethanol and isopropyl alcohol as a solvent. The fresh feed was either directly extracted or pre-treated using an oven and then followed by several stages of extraction. The pre-treatment of fresh feed was carried out in the oven at 70°C for 1 hour. Atmospheric steam distillation was carried out at 100°C for 6 hours using 500 ml of distilled water. In the case of soxhlet extraction, the temperature was set at the boiling point of the solvent for 6 hours. Once soxhlet extraction was complete, the essential oil was separated from the solvent by distillation. After various extraction processes, the essential oils were analyzed for their compound content using GC-MS. Based on the results of the study, the highest yield of 29.04% was obtained from the treated feed using two stages of soxhlet extraction variable with ethanol as solvent.